Studi Kejadian TB BTA Positif Ditinjau dari Aspek Pengetahuan, Sikap dan Lingkungan di Wilayah Kerja Puskesmas Banyuanyar Kota Surakarta - Herlana, Nova, Noor Alis Setiyadi, SKM., MKM., Dr.Ph, Farid Setyo Nugroho, SKM (2014)
Tuberculosis (TB) is an infectious disease caused by bacteria mycrobacterium tuberculosis. The purpose of research to magnitude the knowledge, attitude, and environment that occurs in patients positive TB. Recorded in lock goverment Banyuanyar as muoch as 30 patients positif TB BTA. This is a descriptive research. This research was conducted in March 2014 is the work are of Banyuanyar health centers located in the region of Surakarta Banyuanyar local goverment clinic Surakarta. The sample of the research is 30 patients positive TB . The Data analysis model that is descriptive explain results of each variable frequency of research to distribution results and the percentage. The results of Research patients characteristics most people aged 35-45 years is 8 people (26.7%). The rate of patients school most high school is 10 people (33.3%). The patients most private employment 11 people (36.7%). The results of research to explain rate of knowledge patients about TB and the good of knowledge is 17 people (56,7%), the patients positive TB attitude that good attitude is 21 people (21%). The results of observation lighting home patients qualified conditions 25 home (83.3%), residential density are not qualified conditions 17 home (56,7%), house ventilation qualified is 20 homes (66,7%), type of floor qualified is 26 homes (86.7%), humidity of qualified is 23 homes (76.7%). Research conclusion there is a correlation between, age, education, occupation, knowledge and attitudes with environmental situation have a role in the disease spreading of TB.